Synthesis of 5-(ethylsulfonyl)-2-methoxyaniline: An important pharmacological fragment of VEGFR2 and other inhibitors - Murár, Miroslav; Addová, Gabriela; Boháč, Andrej (Beilstein Journal of Organic Chemistry, 2013)
Background: 5-(Ethylsulfonyl)-2-methoxyaniline (5) is part of the structure in 131 compounds possessing different biological activities. In most cases, they have antitumor properties (112 compounds). Other compounds are described as cardiovascular agents, ion-channel blockers, nervous-system blockers, anti-inflammatory agents, or antidiabetic, antiosteoporotic and hypolipemic species. Compound 5 is a precursor of different protein-kinase inhibitors or enzyme modulators (EGFR, PDGFR, ckit, CDK 2 and 4, MMPs 2, 3, 9 and 13, etc.). The structure of 5 represents a fragment for several powerful inhibitors of VEGFR2, a key angiogenic receptor. Antiangiogenic inhibitors slow down or stop new blood-vessel formation from pre-existing vasculature. Some antiangiogenic drugs inhibiting the VEGFR2 receptor are successfully used in clinics for the treatment of several types of tumours in synergy with chemotherapy (e.g., Nexavar® from Bayer, Sutent® from Pfizer and Votrient® from GlaxoSmithKline, approved by the FDA in 2005, 2006 and 2009, respectively). The structure of 5 is an important pharmacophoric fragment of potent VEGFR2 inhibitors (e.g., AAZ from PDB complex 1Y6A, enzymatic IC50 = 22 nM). Up to now, 25 VEGFR2 inhibitors possessing a fragment of 5 can be found in the literature. Despite the high significance of 5-(ethylsulfonyl)-2-methoxyaniline (5) its preparation has not yet been described.Results: Here we have developed a convenient synthesis of important polyheterosubstituted aniline 5 starting from commercially available 4-methoxybenzene-1-sulfonyl chloride (1) in four steps and 59% overall yield. The target 5-(ethylsulfonyl)-2-methoxyaniline (5) and its synthetic intermediates 2–4 together with a new compound 5-(ethylsulfonyl)-2-methoxy-1,3-dinitrobenzene (4a) have been precisely physicochemically characterised.
Keywords: angiogenesis; pharmacophoric ligand; synthesis of 5-(ethylsulfonyl)-2-methoxyaniline; VEGFR2 tyrosine kinase inhibitors